2013
DOI: 10.1186/1471-2164-14-155
|View full text |Cite
|
Sign up to set email alerts
|

Integrated metabolomics and genomics analysis provides new insights into the fiber elongation process in Ligon lintless-2 mutant cotton (Gossypium hirsutum L.)

Abstract: BackgroundThe length of cotton fiber is an important agronomic trait characteristic that directly affects the quality of yarn and fabric. The cotton (Gossypium hirsutum L.) fiber mutation, Ligon lintless-2, is controlled by a single dominant gene (Li2) and results in extremely shortened lint fibers on mature seeds with no visible pleiotropic effects on vegetative growth and development. The Li2 mutant phenotype provides an ideal model system to study fiber elongation. To understand metabolic processes involved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 75 publications
1
30
0
Order By: Relevance
“…We examined genome-wide gene expression in elongating cotton fiber cells at 8 DPA in Li 1 , Li 2 mutants and WT under different growing conditions, in the field and greenhouse. The time point 8 DPA was selected because our earlier research revealed significant transcript and metabolite changes between the Li 2 and WT NILs during this time of fiber development [ 5 , 6 ]. Approximately 1.06 billion 100 bp reads from 13 libraries, including 9 libraries from field grown plants (this work) and 4 libraries from greenhouse grown plants (previously reported [ 9 ]), were trimmed with Sickle [ 19 ] and mapped to transcripts from the G. raimondii genome reference sequence [ 18 , 20 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We examined genome-wide gene expression in elongating cotton fiber cells at 8 DPA in Li 1 , Li 2 mutants and WT under different growing conditions, in the field and greenhouse. The time point 8 DPA was selected because our earlier research revealed significant transcript and metabolite changes between the Li 2 and WT NILs during this time of fiber development [ 5 , 6 ]. Approximately 1.06 billion 100 bp reads from 13 libraries, including 9 libraries from field grown plants (this work) and 4 libraries from greenhouse grown plants (previously reported [ 9 ]), were trimmed with Sickle [ 19 ] and mapped to transcripts from the G. raimondii genome reference sequence [ 18 , 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the transport of sugars is unlikely altered in short fiber mutants. In our previous report we observed significant reductions in the levels of detected free sugars, sugar alcohols, sugar acids, and sugar phosphates in the Li 2 metabolome; also biological processes associated with carbohydrate biosynthesis were significant down-regulated in the Li 2 transcriptome [ 6 ]. Consequently, detection of low amount of sugars in sap of Li 1 – Li 2 fibers might be the result of reduced de novo synthesis of sugars in mutants.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, phenylpropanoids, particularly flavonoids, are known to inhibit fiber elongation [64], but protect cells from abiotic and biotic stresses [72]. The involvement of flavonoids in fiber processes has been shown in many studies at the transcript, protein, and metabolic levels [12], [13], [20], [64], [73]. Tan et al [64], in particular, showed that the flavonoid naringenin negatively regulates fiber development and that higher levels of naringenin accumulate in short, brown fibers.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, our laboratory conducted extensive analysis of the Li 2 mutant using microarray technology, molecular mapping and metabolomic analysis [25,26]. We developed microsatellite markers associated with the Li 2 genetic locus, and identified transcripts or genes and metabolites that were affected by the Li 2 mutation.…”
Section: Introductionmentioning
confidence: 99%